Case Study On Primigravida In The First Trimester With Emesis Gravidarum In The Tongguh Community Health Center Area Bangkalan Regency - Wendy Tarissa Putri (LPPM Universitas dr. Soebandi, 2024)
Pregnancy is a physiological process characterized by both physical and psychological changes. These changes can cause discomfort, one of which is nausea and vomiting or called emesis gravidarum. The prevalence of pregnant women with emesis gravidarum at Tongguh Health Center from January 8 to February 2, 2024 was 4 out of 10 pregnant women in the first trimester (TM I) or 40%. This case study aims to determine the incidence of emesis gravidarum in primigravida TM I including signs and symptoms, risk factors, complications and management in the Tongguh Health Center area. The case study design is multiple case design with two respondents who have the same criteria, namely primigravida TM I with emesis gravidarum. Data collection was done through interviews and medical record documentation.The results of this case study show that not all respondents experienced signs and symptoms of emesis gravidarum such as nausea, vomiting, weakness and fatigue, decreased appetite and weight. Risk factors of age, nutritional patterns, history of gastritis and stress are not the main factors causing emesis gravidarum. Both respondents did not experience the effects of emesis gravidarum. Both respondents had carried out some of the pharmacological and non-pharmacological treatments.Comprehensive care is needed to overcome emesis gravidarum so that the discomfort can be resolved immediately, including an interpersonal approach to create effective communication in receiving and responding to complaints felt by pregnant women, health education about fulfilling healthy nutritional patterns. Prevention of complications through complementary care such as yoga, gymnastics, acupressure and aromatherapy will help pregnant women with emesis gravidarum to relieve all complaints.